2017
DOI: 10.3892/etm.2017.4619
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid A protects against myocardial ischemia/reperfusion injury by reducing platelet activation and inflammation

Abstract: The aim of the present study was to investigate the protective effect of salvianolic acid A (SAA) on myocardial ischemia/reperfusion injury in rats. SAA (10 mg/kg) or Tirofiban (60 µg/kg) was administered to rats by jugular vein injection 10 min before the initiation of reperfusion. After 3 h of reperfusion, platelet aggregation was measured using an aggregometer and levels of nitric oxide (NO) were detected using an ultraviolet spectrophotometer. Serum levels of cardiac troponin T (cTnT), creatine kinase isoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…SalA alleviated I/R-induced rat brain damage partially via the suppression of FoxO3a/Bim signaling and the downregulation of MMP-9 activity [39,62,63]. SalA also showed antimyocardial I/R damage effects as a consequence of the downregulation of platelet activation and inflammation in rats [41,64]. SalA protected against I/R-induced liver injury via inhibiting TLR4-mediated inflammation in rats [65].…”
Section: Mediators Of Inflammationmentioning
confidence: 92%
See 1 more Smart Citation
“…SalA alleviated I/R-induced rat brain damage partially via the suppression of FoxO3a/Bim signaling and the downregulation of MMP-9 activity [39,62,63]. SalA also showed antimyocardial I/R damage effects as a consequence of the downregulation of platelet activation and inflammation in rats [41,64]. SalA protected against I/R-induced liver injury via inhibiting TLR4-mediated inflammation in rats [65].…”
Section: Mediators Of Inflammationmentioning
confidence: 92%
“…As reported by chemistry research, effective compounds of Danshen are mainly summarized into two categories: lipophilic diterpenoids and watersoluble phenolic acids. The phenolic acids have been identified as natural cardiovascular and cerebrovascular protectants with a variety of pharmacological functions, such as anti-inflammation, antiplatelet aggregation, and antioxidation [36][37][38][39][40][41][42]. These phenolic acids have been accounted for most of the biological activities of Danshen, especially the beneficial impact on ischemia/reperfusion (I/R) damage [43].…”
Section: Introductionmentioning
confidence: 99%
“…Sal-A enhances the expression of proangiogenic factors, such as VEGF and VEGFR2, and elevates the numbers and function of endothelial progenitor cells (EPCs), leading to vasculogenesis and subsequently increasing the blood flow supply in the ischemic myocardium [268] . In addition to MI, Sal-A has also been shown to protect against myocardial I/R injury [273][274][275][276][277] . This protection is achieved by the reduction of myocardial cell apoptosis and damage induced by oxidative stress [274,275,278] , prevention of intracellular calcium overload by blocking L-type calcium current [276] , and inhibition of platelet aggregation and inflammation [277] .…”
Section: Salvianolic Acid Amentioning
confidence: 99%
“…In addition to MI, Sal-A has also been shown to protect against myocardial I/R injury [273][274][275][276][277] . This protection is achieved by the reduction of myocardial cell apoptosis and damage induced by oxidative stress [274,275,278] , prevention of intracellular calcium overload by blocking L-type calcium current [276] , and inhibition of platelet aggregation and inflammation [277] . Although comprehensive investigations of Sal-A in cardiac remodeling are not currently available, a study has revealed that Sal-A acts as a MMP-9 inhibitor to attenuate cardiac fibrosis in the spontaneously hypertensive rat [279] , shedding new light on the cardioprotective effects of Sal-A in pathological remodeling.…”
Section: Salvianolic Acid Amentioning
confidence: 99%
“…Salvianolic acid A (SAA) is one of the most bioactive components extracted from Salvia miltiorrhiza Bunge (Danshen), a traditional Chinese herbal medicine with anti‐inflammation, antiplatelet, antihypertension, antithrombosis, antioxidation, and antirenal disease activities, as well as cardioprotective effects on myocardial infarction . Moreover, in recent years, SAA has been shown to possess other antitumor properties, including suppressive effects on tumor proliferation through targeting endothelin A receptor in DU145 cells and on the lung cancer multidrug resistance gene MDR1 through regulating microRNA expression .…”
Section: Introductionmentioning
confidence: 99%